Differentiation between primary central nervous system lymphoma and glioblastoma: a comparative study of parameters derived from dynamic susceptibility contrast-enhanced perfusion-weighted MRI. Issue 12 (December 2015) - Nakajima, S.; Okada, T.; Yamamoto, A.; Kanagaki, M.; Fushimi, Y.; Okada, T.; Arakawa, Y.; Takagi, Y.; Miyamoto, S.; Togashi, K.
Abstract : Aim: To evaluate the diagnostic performance of parameters derived from dynamic susceptibility contrast-enhanced perfusion-weighted magnetic resonance imaging, including first-pass slope ratio (FSR), which is potentially easier to derive than the other proposed parameters in this study, for differentiating primary central nervous system lymphoma (PCNSL) from glioblastoma. Materials and methods: Twenty-eight patients (10 PCNSLs and 18 glioblastomas) were analysed. Six perfusion parameters — corrected cerebral blood volume ratio (cCBVR), uncorrected CBV ratio (uCBVR), FSR, leakage coefficient (K2 ), percentage of signal-intensity recovery measured at the end of the first-pass (PSRend ), and PSR measured using mean signal-intensity after the first-pass (PSRmean ) — were derived from enhancing areas selected semi-automatically. Comparisons of cCBVR and uCBVR and of PSRend and PSRmean were conducted. The differences between PCNSL and glioblastoma were compared for the six parameters, and their diagnostic performance was evaluated by receiver operating characteristic curve analysis. Results: For both tumours, cCBVR was significantly higher than uCBVR, and PSRend was significantly lower than PSRmean . PCNSL demonstrated lower cCBVR, uCBVR and FSR, and higher K2, PSRend and PSRmean compared with glioblastoma ( p =0.0044 or less). On receiver operating characteristic curve analysis, the areas under the curve were 0.822 for cCBVR, 0.944 for uCBVR, 0.917 for FSR, 0.917 for K2, 0.933 for PSRend, and 0.894 for PSRmean . No significant difference was observed among the parameters, except cCBVR, which was significantly inferior to uCBVR. Conclusions: PCNSL can be differentiated from glioblastoma with high diagnostic value using any of the parameters, except cCBVR. FSR demonstrates high differential performance comparable to the other parameters. Highlights: The diagnostic value of DSC-PWI parameters was evaluated between PCNSL and GBM. Six parameters were compared including first-pass slope ratio proposed in this study. Significant differences were observed between PCNSL and GBM in all six parameters. All parameters showed high diagnostic value except cCBVR that was inferior to uCBVR. FSR analysis is simple and can easily be applied in clinical practice.